Geographer Harm J. de Blij: Academic Contributions and Scientific Communication in Geography - Tang Maolin (Redai dili)
This study aims to broaden the research scope of the history of geography in China. The materials used for the study included Harm J. de Blij's profile (CV), website, autobiography, geography textbooks, and research papers, as well as reviews and research from geography peers. De Blij is a contemporary geography master in political geography, geography textbooks, geography education, and scientific communication in geography. He is a representative of the systems theory school of political geography. He wrote several renowned geography textbooks, including System Political Geography, Human Geography: Culture, Society and Space, Geography: Realms, Regions and Concept, which acted as television precedents for geographical education. and also served as an editor for Journal of Geography and the founding editor of National Geographic Research. He is keen on geographic public speech and has popularized geographical knowledge and concepts. He is probably best known for being the geographic editor of the ABC TV program "Good Morning America" and his high-end science communication books The Power of Place and Why Geography Matters. Because of its innovative character, System Political Geography has scholarly and pedagogical impacts. Most political geography books at the time were dominated by chapters describing the circumstances of selected world regions or reviews of different attributes of states, such as population, resources, and environment. Harm's book encouraged thinking about the conceptual underpinnings of different ideas in political geography: the functional approach and the unified field theory. Second, Harm's book systematically examined particular historical developments of colonialism, the rise of the nation-state, and so on. Third, Harm's book included substantial excerpts from original papers. Human Geography: Culture, Society and Space and Geography: Realms, Regions and Concept are two popular textbooks in Harm's textbooks that act as an introduction to Human Geography and Geography. The Chinese edition of Human Geography: Culture, Society and Space was published by Beijing Normal University Press in 1988, and is considered an important teaching reference for human geography courses. Harm also made important contributions to scholarship on the role of geography in public debate, publishing pieces in the Annals of the Association of American Geographers and Progress in Human Geography and encouraging academic geographers to reach beyond the confines of the academy. Harm's lifelong thinking about political geography culminated in his book Why Geography Matters, which was revised and expanded several years later (de Blij 2012). Harm set a good example of high-quality geography textbooks based on academic research, actively spreading and promoting geography thinking, and writing popular science works and newspaper column articles based on hot issues from the perspective of geography. We can learn a lot from Harm J. de Blij on the main three aspects.